Injustice and abuse: the fruits of a money-focused society in «Paco Yunque» - Wolfersberger, Christopher (2024)
The short story “Paco Yunque,” written by Cesar Vallejo, tells the story of a country boy who is abused by Humberto Grieve, the son of a wealthy family. This tale of injustice provides a commentary on the relationships that exist between the rich and the poor. It demonstrates how a focus on money creates dominators and dominated, and that this outcome is so fundamental to capitalist society that the effects are seen even in children at school. This essay analyzes various literary tools that are used to express this message and inspire in the reader the desire to fight for a better world.